Irtysh: Environmental Risks and Threats - Sydykov Yerlan; Sailaubay Yerlan; Maslov Khalil; Zhanbossinova Albina; Detochkina Violetta (BIO Web of Conferences)
Water is the source of life on Earth and a fundamental resource that plays a crucial role in environmental, economic, societal, and security- related issues. It is one of the key factors determining the stability of any state. The concept of hydro-hegemony, as used by the authors, highlights the hydropolitical dimensions of the issue and the ecological vulnerability of the Irtysh River, which flows through China, Kazakhstan, and Russia. The geographical positioning of the Irtysh River, with its source in China, allows the upstream country to control water intake levels, potentially disadvantaging the downstream nations, Kazakhstan and Russia. The ecosystem of Kazakhstan’s Irtysh and Ili river basins is highly dependent on China’s hydropolitical strategies, as a network of lakes-including Alakol, Zaisan, and Balkhash – as well as artificial reservoirs fed by these rivers, are at environmental risk. The aim of this research is to assess the impact of hydro-hegemony on the ecological status of the Irtysh River and the potential consequences for Kazakhstan. China’s expanding agricultural policies, which include the expansion of cultivated areas and the construction of large-scale dams and reservoirs, have increased water withdrawals from rivers that flow into Kazakhstan. An analytical review of the available materials indicates that China is actively developing environmentally sustainable water management technologies, whereas Kazakhstan continues to experience water pollution from industrial enterprises, posing a potential threat to the river ecosystem.